The state of implementation the decentralization in Ukraine - Esh, Svetlana; Gerasimenko, Daria (My University, 2020)
The development of local self-government in Ukraine is accompanied by decentralization processes aimed at the effective activity of local authorities and improvement of the socioeconomic standard of living of the population. The article examines the current state of decentralization reform in Ukraine The problems and risks that accompany the processes of decentralization in modem economic conditions are substantiated. Changes in the legal regulation of decentralization reform and their impact on the development of local self-government are considered. The purpose of the study is to analyze the current state and prospects of decentralization, determine the nature and place of united territorial communities (UTC) in the development of local self-government, substantiate the problems associated with the processes of decentralization and generalized prospects for the further development of UTC in modem economic conditions. During the study of decentralization processes, common scientific and special methods were used. The methods of comparison and grouping are used to analyze the processes of creation of UTC, the statistical method helps to compare the dynamics of UTC formation on a territorial basis, conduct economic data concerning the financial resources of the community. The methodology of the systematic approach involves a comprehensive study of the factors that accompany and influence decentralization processes. Method of generalization is used in drawing conclusions and recommendations. The article provides the dynamics of the formation of the UTC over 5 years, the basic and additional criteria, which are needed to determine community capacity, were analyzed, a comparative characterization of the capacity of communities in the regions of Ukraine was conducted and the capacity rating was justified. Розвиток місцевого самоврядування в Україні супроводжується процесами децентралізації, які направлені на ефективну діяльність органів місцевої влади та підвищення соціально-економічного рівня життя населення. У статті досліджено поточний стан реформи децентралізації в Україні. Обґрунтовано проблеми та ризики, які супроводжують процеси децентралізації в сучасних умовах господарювання. Розглянуто зміни у нормативно-правовому регулюванні реформи децентралізації та їхній вплив на розвиток місцевого самоврядування. Здійснено аналіз сучасного стану та перспектив розвитку децентралізації, визначення суті та місця ОТГу розвитку місцевого самоврядування, обґрунтовано оцінку проблем, які пов’язані з процесами децентралізації, та узагальнено перспективи подальшого розвитку ОТГ у сучасних умовах господарювання. Під час дослідження процесів децентралізації використані загальнонаукові та спеціальні методи. За допомогою методів порівняння та групування аналізуються процеси створення об ’єднаних територіальних громад (ОТГ), статистичний метод допомагає порівняти динаміку формування ОТГ за територіальним принципом, провести обробку економічних даних, що стосуються фінансових ресурсів громади. Методологія системного підходу передбачає комплексне вивчення факторів, які супроводжують процеси децентралізації та впливають на них. Під час розробки висновків і рекомендацій використовується метод узагальнення. Описано динаміку формування ОТГ протягом п ’яти років, проаналізовано базові і додаткові критерії, необхідні для визначення спроможності громади, проведено порівняльну характеристику спроможності громад областей України, обґрунтовано рейтинг спроможності.
Keywords: decentralization; reform; united territorial collectives; local finance; local government; децентралізація; реформування; об’єднані територіальні громади; місцеві фінанси; органи місцевого самоврядування; кафедра фінансів